Penilaian Organolpetik Dan Analisis Keamanan Sediaan Lipstik Berbahan Dasar Lemak Tengkawang - Gusti, R Esa Pangersa; Pasaribu, Gunawan Tri Sandi; Dahlian, Erik (Jurnal Penelitian Hasil Hutan, 2023)
Tengkawang fruit can be processed into a form of high economic value fat. This is due to its properties which are similar to cocoa butter so it is widely used as Cocoa Butter Substitutes (CBS) on various cocoa fat products, one of which is lipstick. Manufacturing and analysis of the performance of tengkawang fat-based lipstick has been done. However, to ensure a cosmetic product is safe to use, it is necessary to use safety and irritation tests. This study aims to analyze the safety level of the tengkawang fat-based lipstick through an organoleptic test, microbial contamination, and simple irritation test. There are four lipstick formulations used in this activity, the two best formulations (m3 and m5) from the previous year's research, two modification formulas of the previous formula (m3i and m5i) and commercial lipstick as a comparison (control). Organoleptic tests will be carried out on four types of lipstick formulas which include texture, gloss, odor, color and spreadability of the lipstick. This test uses a scoring system. panelists for the organoleptic test were 34 people with an age range of 17-45 years. Another analysis is the microbial contamination and simple irritation tests following the procedures of the Indonesian National Standard (SNI) 16-4769-1998 concerning lipstick. The microbial contamination test was carried out in two stages, the first for fresh lipstick (finished production) and the second for lipstick that had been stored for four months. A simple irritation test analysis was carried out by applying lipstick to the mice's skin. The results showed that from an organoleptic point of view, the lipstick with the formula m5 was the most preferred by the panelists. In terms of safety for use, the microbial contamination test showed no presence of microbes in the lipstick preparation. A simple irritation test showed no signs of irritation after 24, 36, 48, and 136 hours of observation, which indicated that the lipstick made from tengkawang fat was safe to use.